2016
DOI: 10.1038/nm.4054
|View full text |Cite
|
Sign up to set email alerts
|

p16Ink4a-induced senescence of pancreatic beta cells enhances insulin secretion

Abstract: Cellular senescence is thought to contribute to age-associated deterioration of tissue physiology. The senescence effector p16Ink4a is expressed in pancreatic beta cells during aging and limits their proliferative potential; however, its effects on beta cell function are poorly characterized. We found that beta cell-specific activation of p16Ink4a in transgenic mice enhances glucose-stimulated insulin secretion (GSIS). In mice with diabetes, this leads to improved glucose homeostasis, providing an unexpected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
233
5
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(268 citation statements)
references
References 65 publications
24
233
5
6
Order By: Relevance
“…Broad molecular and epigenetic changes occur as β-cells mature and age, with well-documented loss of EZH2 and BMI1, an increase in cell-cycle inhibitors such as P16 INK4a and p18 INK4c , and epigenetic changes 15,88,89 . Some of these changes seem to improve β-cell function 90 , but they may broadly suppress the ability of β-cells to respond to proliferative stimuli. There is longstanding evidence that insulin and glucose, both of which are elevated in obesity or insulin resistance, may directly stimulate β-cell proliferation 9193 .…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
“…Broad molecular and epigenetic changes occur as β-cells mature and age, with well-documented loss of EZH2 and BMI1, an increase in cell-cycle inhibitors such as P16 INK4a and p18 INK4c , and epigenetic changes 15,88,89 . Some of these changes seem to improve β-cell function 90 , but they may broadly suppress the ability of β-cells to respond to proliferative stimuli. There is longstanding evidence that insulin and glucose, both of which are elevated in obesity or insulin resistance, may directly stimulate β-cell proliferation 9193 .…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
“…In humans, the accumulation of senescent markers has been demonstrated in the skin, T lymphocytes, atherosclerotic lesions, insulin-producing β cells, kidney, endothelium, visceral fat, joint cartilage, cardiac muscle, liver, and many others tissues 98,101107 . Some tissues are likely to have a greater propensity to developing cellular senescence than others, but research in this area is scarce.…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 99%
“…A major impediment for such layout is the harmless impact of SIR on insulin despite its senescence triggering effect. Although recent observations shown that b-cells undergoing senescence in absence of external stress have an enhanced insulin production compared to their regular counterparts [40], the issue of stress-induced premature senescence remains challenging.…”
Section: Mitochondrial Dysfunction In Endocrine B-cellsmentioning
confidence: 99%